Effect of the presence of iron-modified montmorillonite (Fe-MMT) on the thermal and photo-degradation of polycaprolactone (PCL) nanofiber mats - Montenegro, Feliz Patricia D.; Samson, Martha Elenor B.
The booming mining industry in the Philippines requires the development of sustainable alternative waste water treatment methods. Polycaprolactone mats have been utilized as filters to remove toxic heavy metals from waste water. To prevent the accumulation of these mats after they have been used, a study on the degradation of PCL/Fe-MMT mats would be necessary. In this study, the thermal and photo degradation of pure polycaprolactone (PCL) and polycaprolactone-iron-montmorillonite (PCL/Fe-MMT) nanofiber mats were studied in order to determine whether these methods were viable degradation options. Electrospun PCL and PCL/Fe-MMT nanofiber mats were studied via Thermogravimetric Analysis for thermal degradation. The presence of Fe-MMT resulted to a decrease in degradation temperature upon TG analysis. This observation was true regardless of the environment, N2 or O2. However, the presence of clay in the polymer resulted to residue after thermal analysis. For photo degradation analysis, the mats was exposed to germicidal lamp (UVC = 254 nm) for a total of 80 hours. A 20% increase in mass was observed for the neat PCL mats compared to a 12% increase in PCL/Fe-MMT. Exposure to UV radiation led the mats to lose their nanofiber structure in addition to its observable yellowing. FTIR analysis showed no broken bonds of the polymer after irradiation, but a new peak at 2358 cm-1 was observed for irradiated PCL and PCL/Fe-MMT and was attributed to CO2. The more defined CO2 peak in PCL further confirmed that PCL underwent greater degradation than PCL/Fe-MMT. Irradiated PCL/Fe-MMT showed negligible change in degradation temperature compared to fresh PCL/Fe-MMT, and irradiated PCL had a lower degradation temperature compared to fresh PCL. The changes brought about by the presence of Fe-MMT in PCL for both degradation methods were due to the introduction of the barrier effect brought about the clay. Modifying the clay with Fe3+ further enhanced the said effect; thus resulting to a decrease in degradation in both methods.